(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article is focused on professional decision-making by a linguist, on the one hand, an engineer, on the other one, in the process of technical translation. Research on professional interactions has a fairly solid foundation in linguistics. Professional discourse is presented, first of all, as social interaction of an institutional type, during which the communicative interaction of people, built on the principle of hierarchy, reflects the overall goal - to obtain the product of their joint activity, expressed, ultimately, in material values. This definition of professional and business discourse presents its essential characteristics and provides grounds for classifying its subspecies. The differences in mental schemata hereto are determined by the differences in the cognition of the professional in question.